Collapsing Commonwealth: Luis Rafael Sánchez's La guaracha del Macho Camacho. - SELCKE, GRETCHEN (Afro-Hispanic Review)
The article talks about Luis Rafael Sánchez's La guaracha del Macho Camacho novel that continues to radically re-imagine Puerto Rican politics. It mentions about the established hierarchy, rendering ridiculous the repetitive cycle of status referenda and economic and political stagnation that dominate Puerto Rico as a Commonwealth.